Delete
Share
This Question is Closed
goformit100
Best Response
You've already chosen the best response.
0
=0
hartnn
Best Response
You've already chosen the best response.
1
just put x=-1 in f(x)
davian
Best Response
You've already chosen the best response.
0
\[fx=x ^{2}-4x+3/x+2\]
hartnn
Best Response
You've already chosen the best response.
1
did u try to put x=-1 there ?
davian
Best Response
You've already chosen the best response.
0
what do you mean?
hartnn
Best Response
You've already chosen the best response.
1
replace all x in f(x) by -1
hartnn
Best Response
You've already chosen the best response.
1
f(-1)=(-1)^2−4(-1)+3/(-1)+2 = ?
davian
Best Response
You've already chosen the best response.
0
wait what ..sorry i still dont understand!
davian
Best Response
You've already chosen the best response.
0
can you write it out in simple terms?
hartnn
Best Response
You've already chosen the best response.
1
u have f(x) right?
u need f(-1) right?
so just replace all x in f(x) by -1
for example:
if f(x) =x^3 and i need f(-1)
so i would write
f(-1)= (-1)^3 = -1
did u understand this?
can u do your problem now ?
davian
Best Response
You've already chosen the best response.
0
ill try hold on